Ru-based catalyst, preparation method and application
By using a stable Ru-based catalyst, the synergistic effect of Ru-based activity center, co-catalyst and modified composite support is solved, and the problem of difficult to take into account both the catalyst activity and stability when preparing chlorine gas by catalytic oxidation of HCl is achieved, and efficient, economical and environmentally friendly chlorine preparation is achieved.
Patent Information
- Application Number
- CN202411912085.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
Existing catalysts are difficult to take into account high activity and high stability when catalyzed oxidation of HCl to prepare chlorine, resulting in increased reaction costs and environmental pollution risks.
A stable Ru-based catalyst is used, which consists of active ingredient Ru, a co-catalyst and a modified composite support. The activity and stability of the catalyst are improved through specific raw material ratios and preparation methods.
It significantly improves catalytic activity and long-term stability, reduces the frequency of catalyst loss and replacement, and reduces production costs and environmental pollution risks.
Smart Images

Figure CN119633862A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a Ru-based catalyst, a preparation method and an application thereof, and more particularly to a stable Ru-based catalyst, a preparation method and a method for preparing chlorine by catalytic oxidation of HCl. Background Art
[0002] Hydrogen chloride and chlorine are both important chemical products and industrial raw materials. Chlorine plays a key role in the production of polyurethane, polyvinyl chloride, epoxy resin, synthetic rubber and some agricultural chemicals. However, for every mole of chlorine consumed in industry, an equal mole of hydrogen chloride gas will be produced. Hydrogen chloride gas is cheap, has a small demand and is difficult to handle. Therefore, it is crucial to achieve the recycling of chlorine.
[0003] At present, catalytic oxidation has become an ideal way to achieve the recycling of chlorine due to its advantages such as low energy consumption, simple reactants and no side reactions. In recent years, catalysts for the catalytic oxidation of hydrogen chloride have continued to emerge, including copper-based, chromium-based, cerium-based catalysts, etc., but these catalysts generally have problems such as high main agent content, high reaction temperature, low conversion rate and serious catalyst loss, which often lead to increased reaction costs and cause environmental pollution consequences caused by waste catalysts. Although the highly active Ru-based catalyst with titanium oxide as the carrier can achieve a high conversion rate of hydrogen chloride at a relatively low temperature, in actual applications, local overheating of the reactor can easily cause the catalyst to deactivate quickly, and the catalyst loss phenomenon is significant during long-term operation.
[0004] CN101663092A discloses a technical solution using zirconium compounds, cerium compounds, alkali metal compounds and alkaline earth metal compounds as RuO2-based catalyst promoters. By adding halide promoters in a specific molar ratio, the long-term stability of the catalyst is effectively prolonged, the replacement frequency is reduced, and the cost is reduced. Some promoters optimize the catalytic activity under specific conditions and improve the reaction efficiency. At the same time, the patent gives detailed ranges and preferred values of reaction process parameters, provides operational guidance for industrial production, helps to optimize process conditions, improve the controllability and stability of production, and achieve efficient, economical and environmentally friendly production. However, the solution still has some technical defects that need to be improved, such as high content of RuO2 in the main agent, resulting in increased costs and low resource utilization efficiency; high reaction temperature leads to high energy consumption, and increases equipment requirements and maintenance costs; low conversion rate causes waste of raw materials and complicated subsequent treatment; serious catalyst loss leads to increased costs and environmental pollution risks, etc.
[0005] CN109453764A discloses a RuO2-based catalyst with an alkali metal component and a transition metal component as a promoter and silicon dioxide as a carrier modification agent. Compared with a catalyst without adding a promoter and a carrier modifier, after 500 hours of reaction, the HCl conversion rate decreases by about 10%, which improves the initial activity of the catalyst to a certain extent; however, this method also has shortcomings, such as a high content of precious metal Ru, a high reaction temperature, and a large room for improvement in conversion rate.
[0006] Ni et al. elaborated on the Deacon process for the catalytic oxidation of hydrogen chloride to produce chlorine (Polyvinyl Chloride 2014; 42(5):9-12), and systematically sorted out the development history of the Deacon process in terms of catalyst improvement (copper, chromium, ruthenium, etc.) and reactor optimization (fixed bed, fluidized bed), providing a comprehensive reference for research in this field. The catalysts with titanium oxide (rutile TiO2 has higher catalytic efficiency), zirconium oxide or aluminum oxide as carriers and fixed bed tubular reactors can achieve a hydrogen chloride conversion rate of 95.9%. However, this process has many problems. Due to the large amount of catalyst used, the production cost of the process for the catalytic oxidation of hydrogen chloride to produce chlorine is greatly increased, which weakens the economic feasibility and market competitiveness. In long-term operation, there is a risk of stability of active components, which may reduce catalyst activity, shorten service life and increase replacement cost due to volatilization or loss. In large-scale production, it faces challenges of scale-up effect, such as uneven loading, heat transfer and material distribution affecting the reaction effect. In addition, the scarcity of ruthenium may also lead to unstable supply and affect production continuity.
[0007] In summary, it is difficult for existing catalysts to achieve both high activity and high stability. Usually, in order to improve the activity of the catalyst, the reaction temperature can only be increased or the proportion of the reaction gas phase can be changed. However, due to the exothermic nature of the reaction of ruthenium-containing catalysts, these measures are prone to cause problems such as high-temperature sintering of the catalyst and serious loss of components, thereby increasing the preparation cost. Therefore, the development of a catalyst for the catalytic oxidation of HCl to produce chlorine that has both high activity and high stability has become a technical problem that needs to be solved urgently. Summary of the invention
[0008] In view of the deficiencies of the above-mentioned prior art, the present invention provides a stable Ru-based hydrogen chloride catalytic oxidant and a preparation method thereof. The catalyst prepared by the method is applied to the oxidation of hydrogen chloride to prepare chlorine, and exhibits a high hydrogen chloride conversion rate, high reaction activity, long-term stability and high temperature resistance. The alkali metal or alkaline earth metal in the catalyst closely combines and interacts with the Ru active component, reducing the aggregation and growth of Ru particles, which is beneficial to improving the activity stability of the catalyst; the carrier modifier tightly fixes the Ru particles on the carrier surface through the bonding effect with Ru, greatly reducing the loss of Ru and extending the service life of the catalyst. The catalyst preparation method is simple, easy to repeat, good in stability, and has a good application prospect. The specific technical scheme is as follows:
[0009] A Ru-based catalyst, the catalyst is composed of an active ingredient Ru, a promoter, and a modified composite carrier. In the catalyst, based on the total mass of the catalyst and calculated as a Ru element, the loading amount of Ru is 0.1-5wt%, based on the total mass of the catalyst and calculated as a metal element, the content of the promoter is 0-20wt%; the specific surface area of the catalyst is 50-300m 2 / g, when the catalyst catalyzes the oxidation of HCl to prepare chlorine, the initial conversion rate of HCl is ≤89.95%, the conversion rate of HCl after catalytic deactivation at 650°C is ≤86.24%, and the conversion retention rate is ≤95.88%.
[0010] A method for preparing the Ru-based catalyst according to claim 1, comprising the following steps:
[0011] Step 1: Preparation of modified composite carrier
[0012] The modifier is dissolved in deionized water to prepare a modifier solution; the carrier and the modifier solution are mixed, stirred evenly, kneaded, extruded, and then dried in an oven at 100-200° C. for 5-20 hours, and then calcined at 500-1000° C. for 2-10 hours to obtain the modified composite carrier;
[0013] Step 2: Preparation of Ru-based catalyst
[0014] The promoter is dissolved in deionized water, and a soluble salt of Ru is added to obtain a salt solution containing Ru groups. The modified composite carrier is immersed in the salt solution containing Ru groups, dried at 80-150° C. for 5-20 hours, and then calcined at 200-500° C. for 2-10 hours to obtain the Ru-based catalyst.
[0015] Furthermore, in step 1, the modifier is a soluble sulfur-containing oxygen acid salt and / or a soluble phosphorus-containing oxygen acid salt, and the content of the modifier is 0-20wt% in terms of sulfur or phosphorus based on the mass of the catalyst; the carrier is a mixture of one or more of TiO2 and other metal oxides or non-metal oxides.
[0016] Furthermore, in step 1, the soluble sulfur-containing and oxygen-containing acid salt is taken from one or a mixture of more than one of sulfates, hydrogen sulfates, persulfates, pyrosulfates, sulfites, and thiosulfates of ammonium, lithium, sodium, potassium, cesium, magnesium, calcium, strontium, and barium; the soluble phosphorus-containing and oxygen-containing acid salt is selected from one or a mixture of more than one of phosphates, hydrogen phosphates, dihydrogen phosphates, pyrophosphates, and acid pyrophosphates of ammonium, lithium, sodium, potassium, cesium, magnesium, calcium, strontium, and barium.
[0017] Furthermore, in step 1, the non-metallic oxide is selected from any one of SiO2 and B2O3 or a mixture of two of them; the metal oxide is selected from any one of Al2O3, ZrO2, SnO2 or a mixture of two or more of them.
[0018] Furthermore, in step 2, the co-catalyst is selected from one or a mixture of two or more of soluble alkali metal salts and / or alkaline earth metal chlorides, nitrates, acetates, formates, oxalates, sulfates, and phosphates; the soluble Ru salt is selected from one or a mixture of more than one of ruthenium chloride, ruthenium bromide, ruthenium iodide, ruthenium acetate, potassium chlororuthenate, and ammonium chlororuthenate.
[0019] Furthermore, the molar ratio of the co-catalyst to Ru is (0.1-5):1.
[0020] Furthermore, the mass ratio of Ru to the carrier is 1:(20-1000).
[0021] Furthermore, in the XRD spectrum, characteristic diffraction peaks of (110), (004), (200), (105), and (211) of rutile TiO2 appeared at 27.4°, 38.0°, 48.0°, 54.0°, and 62.7°, proving that the TiO2 in the carrier is a rutile crystal form or a mixed crystal form of rutile and anatase, and in the modified composite carrier, the TiO2 content is ≥40wt% based on the mass of the modified composite carrier.
[0022] A method for catalytic oxidation of HCl, wherein the method uses the Ru-based catalyst according to claim 1, and the specific steps are as follows:
[0023] The Ru-based catalyst is added to a fixed bed reactor, the reaction temperature is controlled at 300-400°C, and a mixed gas of HCl and O2 is introduced into the reactor at a gas space velocity of 5000-10000h -1 , wherein the molar ratio of HCl:O2 is (2-20):1, and the reaction time is 4-30h at 300-400°C; then the reaction temperature is raised to 650-750°C for high-temperature catalytic deactivation of the catalyst, and after deactivation for 10-20h, the temperature is lowered again to 300-400°C for continuous reaction for 4-30h.
[0024] Furthermore, the initial conversion rate of HCl is ≤89.95%, the conversion rate of HCl after accelerated deactivation at 650° C. is ≤86.24%, and the conversion retention rate is ≤95.88%.
[0025] The beneficial effects of the present invention are as follows:
[0026] 1. Significantly improve catalytic activity
[0027] The present invention prepares a stable Ru-based catalyst by using special raw materials and specific ratios. When the catalyst is used for catalytic oxidation of HCl to prepare chlorine, the catalyst unexpectedly shows an initial conversion rate significantly higher than that of the comparative example. This is due to the synergistic effect between the Ru-based active center, the co-catalyst and the modified composite carrier, which jointly promotes the reaction and the improvement of the conversion rate, and provides the possibility of obtaining more chlorine products in a shorter time in industrial production, thereby improving the overall production efficiency. This beneficial effect is mainly attributed to:
[0028] ① Effective interaction between active centers and reactants: Ru, as an active ingredient, has a unique electronic structure that enables it to effectively adsorb and activate HCl and O2 molecules. Ru atoms can provide suitable adsorption sites, reduce the activation energy of reactant molecules, and promote the reaction. During the reaction, HCl molecules are adsorbed on the Ru surface, and the electron cloud of Ru interacts with the H-Cl bond in the HCl molecule, polarizing and weakening the H-Cl bond, making it easier to break to form H+ and Cl- ions. At the same time, O2 molecules are also adsorbed and activated on the Ru surface to form active oxygen species (such as O- or O2-). These activated reactant species react on the Ru surface to generate Cl2 and H2O.
[0029] ② The promoting effect of the co-catalyst: The presence of the co-catalyst further enhances the activity of the catalyst. Alkali metals or alkaline earth metals as co-catalysts may promote the reaction by changing the electron density of Ru or providing additional active sites. For example, alkali metal ions can form ionic bonds or weak chemical bonds with Ru, adjusting the electronic properties of Ru, making it more conducive to the adsorption and activation of reactants. At the same time, the co-catalyst may also affect the diffusion rate of reactants on the catalyst surface, making it easier for reactants to reach the active center and increasing the reaction rate.
[0030] ③Synergistic effect of modified composite carrier: The modified composite carrier not only provides dispersion and support for active ingredients and co-catalysts, but also participates in the catalytic reaction process. TiO2, as the main carrier component, has a specific crystal structure and surface properties in its rutile form or a mixed form of rutile and anatase, which is conducive to the adsorption and desorption of reactants and products. The interaction between the modifier sulfur-containing and oxygen-containing acid salts and / or phosphorus-containing and oxygen-containing acid salts and the TiO2 carrier changes the surface acidity and alkalinity and electronic properties of the carrier, thereby optimizing the dispersion state of active ingredients and co-catalysts and improving their activity. In addition, other metal oxides or non-metal oxides (such as Al2O3, SiO2, etc.) in the modified composite carrier also produce a synergistic effect with TiO2, further improving the performance of the catalyst. For example, Al2O3 can increase the thermal stability and mechanical strength of the carrier, while adjusting the surface acidity of the carrier to make it more suitable for the adsorption and reaction of reactants.
[0031] 2. Excellent stability and high temperature resistance
[0032] From the stability analysis, the catalyst of the present invention has no obvious deactivation after 1000h of continuous reaction, and can maintain stable catalytic performance during long-term operation, which is crucial for the continuous and stable operation of industrial production, avoiding the time cost and economic cost caused by frequent shutdown and replacement of catalysts due to catalyst deactivation; in the high-temperature accelerated deactivation experiment, the HCl conversion rate can still reach 86.24%, and the conversion rate retention rate is as high as 95.88%, which is much higher than that of Comparative Example 1 (61.27% and 71.70%), indicating that the catalyst of the present invention has more stable structure and performance under high temperature conditions, can adapt to complex working conditions such as temperature fluctuations that may occur in industrial production, and ensure the stability and reliability of the production process. This stability and high temperature resistance are mainly attributed to:
[0033] ① Stable dispersion of active components: The co-catalyst and the Ru active component are closely combined and interact with each other, which reduces the aggregation and growth tendency of Ru particles. Under high temperature conditions, Ru particles in the Ru-based catalysts of the prior art are prone to migration and aggregation, resulting in a reduction in active sites and catalyst deactivation. The presence of the co-catalyst can fix the Ru particles on the surface of the carrier by forming chemical bonds or physical adsorption, preventing them from agglomerating. For example, alkali metal or alkaline earth metal ions can form stable compounds or complexes with Ru, so that the Ru particles maintain a small size and a high degree of dispersion, thereby maintaining the activity of the catalyst. This stable dispersion state can be maintained under long-term reaction and high-temperature conditions, ensuring the stability of the catalyst;
[0034] ② Structural stability of the carrier: The structure of the modified composite carrier has high stability at high temperatures. By modifying and calcining the carrier during the preparation process, the crystal structure of the carrier is optimized and the thermal stability is enhanced. The rutile crystal form of TiO2 itself has good thermal stability, and the introduction of the modifier may further improve the high temperature resistance of the carrier. For example, phosphorus-containing and oxygen-containing salts react with the surface of the carrier at high temperatures to form stable chemical bonds and enhance the structural integrity of the carrier. At the same time, other metal oxides in the carrier (such as ZrO2, SnO2, etc.) can also improve the thermal stability of the carrier and prevent the carrier from phase change or sintering at high temperatures, thereby ensuring the overall structural stability of the catalyst;
[0035] ③ Strong interaction between active components and carriers: The carrier modifier tightly fixes Ru particles on the carrier surface through bonding with Ru, which greatly reduces the loss of Ru. During the reaction process, especially under high temperature and air flow conditions, the active components of the Ru-based catalysts in the prior art are easily lost from the carrier surface, resulting in a decrease in catalyst activity. A strong chemical bond or chemical bonding is formed between the modifier in the present invention and Ru, so that Ru is firmly attached to the carrier. This strong interaction not only prevents the loss of Ru, but also ensures the uniform distribution and stable existence of the active components on the carrier surface, so that the catalyst can still maintain high activity and stability under long-term operation and high temperature conditions.
[0036] 3. Reduce costs and be environmentally friendly
[0037] Since the catalyst has high activity and stability, the amount of catalyst used can be reduced during the reaction, thereby reducing production costs. At the same time, a stable catalyst means less frequent replacement, which not only reduces production interruption time caused by catalyst replacement and indirectly reduces time costs, but also reduces the amount of waste catalyst generated and reduces potential environmental pollution risks. It is in line with the concept of sustainable development and helps companies to fulfill their environmental protection responsibilities while improving economic benefits, enhance their social image and competitiveness, and have more advantages in long-term development. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The conversion trend of the catalysts of Example 1 (black) and Comparative Example 1 (red) in the reaction of preparing chlorine by catalytic oxidation of HCl is shown below:
[0039] Keeping the gas composition ventilation volume and reaction temperature constant, samples were taken every 4 hours for the two groups of reactions, and the average of the test results every 24 hours was calculated. After 1000 hours of continuous reaction, the stability of the catalyst was analyzed and the conversion rate trend was recorded in Figure 1 . DETAILED DESCRIPTION
[0040] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0041] Preparation method of the aforementioned Ru-based catalyst
[0042] In Examples 1-5, a series of catalysts with different modified composite supports were prepared by adjusting the composition and dosage of the modifier, support and co-catalyst. The synergistic mechanism of the modifier, support, co-catalyst and active ingredient Ru group in the catalytic oxidation of HCl to produce chlorine was explained by a specific ratio. The specific implementation plan is as follows:
[0043] Example 1
[0044] Step 1: Preparation of modified composite carrier
[0045] 1.1097 g of Na2SO4 and 2.6468 g of Na3PO4 were dissolved in 50 mL of deionized water to prepare a modifier solution; a mixture of 90 g of TiO2 and 10 g of Al2O3 was mixed with the modifier solution, kneaded, extruded, and then dried at 100°C for 10 h, and then calcined at 700°C for 5 h to obtain a modified composite carrier;
[0046] Step 2: Preparation of Ru-based catalyst
[0047] 1.9115 g of KCl was dissolved in 50 mL of deionized water, and then 4.4611 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The modified composite support was immersed in the salt solution containing a Ru group, dried at 120°C for 5 h, and then calcined at 450°C for 5 h to obtain the Ru-based catalyst, which was recorded as catalyst 1.
[0048] Example 2
[0049] Step 1: Preparation of modified composite carrier
[0050] 2.6468 g of Na3PO4 was dissolved in 60 mL of deionized water to prepare a modifier solution; a mixture of 90 g of TiO2 and 10 g of SiO2 was mixed with the modifier solution, kneaded, extruded, and then dried at 120°C for 10 h, and then calcined at 800°C for 5 h to obtain a modified composite carrier;
[0051] Step 2: Preparation of Ru-based catalyst
[0052] 1.9115 g of KCl was dissolved in 65 mL of deionized water, and then 4.4611 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The modified composite support was immersed in the salt solution containing a Ru group, dried at 120°C for 20 h, and then calcined at 500°C for 5 h to obtain the Ru-based catalyst, which was recorded as catalyst 2.
[0053] Example 3
[0054] Step 1: Preparation of modified composite carrier
[0055] 1.1097 g of Na2SO4 was dissolved in 45 mL of deionized water to prepare a modifier solution; a mixture of 80 g of TiO2 and 10 g of Al2O3 was mixed with the modifier solution, kneaded, extruded, and then dried at 100°C for 10 h, and then calcined at 700°C for 5 h to obtain a modified composite carrier;
[0056] Step 2: Preparation of Ru-based catalyst
[0057] 1.9115 g of KCl was dissolved in 50 mL of deionized water, and then 4.4611 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The modified composite support was immersed in the salt solution containing a Ru group, dried at 120°C for 5 h, and then calcined at 400°C for 6 h to obtain the Ru-based catalyst, which was recorded as catalyst 3.
[0058] Example 4
[0059] Step 1: Preparation of modified composite carrier
[0060] 0.2219 g of Na2SO4 and 0.5294 g of Na3PO4 were dissolved in 55 mL of deionized water to prepare a modifier solution; a mixture of 70 g of TiO2 and 30 g of SnO2 was mixed with the modifier solution, kneaded, extruded, and then dried at 120°C for 10 h, and then calcined at 800°C for 4 h to obtain a modified composite carrier;
[0061] Step 2: Preparation of Ru-based catalyst
[0062] 1.9115 g of KCl was dissolved in 50 mL of deionized water, and then 4.4611 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The modified composite support was immersed in the salt solution containing a Ru group, dried at 120°C for 15 h, and then calcined at 400°C for 6 h to obtain the Ru-based catalyst, which was recorded as catalyst 4.
[0063] Example 5
[0064] Step 1: Preparation of modified composite carrier
[0065] 1.1097 g of Na2SO4 and 2.6468 g of Na3PO4 were dissolved in 50 mL of deionized water to prepare a modifier solution; a mixture of 70 g of TiO2 and 30 g of Al2O3 was mixed with the modifier solution, kneaded, extruded, and then dried at 110°C for 20 h, and then calcined at 900°C for 5 h to obtain a modified composite carrier;
[0066] Step 2: Preparation of Ru-based catalyst
[0067] 0.9556 g of KCl was dissolved in 60 mL of deionized water, and then 2.2306 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The modified composite support was immersed in the salt solution containing a Ru group, dried at 120°C for 15 h, and then calcined at 450°C for 8 h to obtain the Ru-based catalyst, which was recorded as catalyst 5.
[0068] Comparative Example 1
[0069] Step 1: Prepare the carrier
[0070] Mix 90g of TiO2 and 10g of Al2O3, add 50mL of deionized water, stir evenly, knead, extrude, then dry at 100℃ for 10h, and then calcine at 900℃ for 5h to obtain a carrier;
[0071] Step 2: Preparation of Ru-based catalyst
[0072] 1.9115 g of KCl was dissolved in 50 mL of deionized water, and then 4.4611 g of RuCl3·3H2O was added to obtain a salt solution containing a Ru group. The support was immersed in the salt solution containing a Ru group, dried at 120°C for 5 h, and then calcined at 450°C for 5 h to obtain the Ru-based catalyst, which was recorded as catalyst 6.
[0073] Comparative Example 2
[0074] Step 1: Prepare the carrier
[0075] Mix 90g of TiO2 and 10g of SiO2, add 60mL of deionized water, stir evenly, knead, extrude, then dry at 120℃ for 10h, and then calcine at 800℃ for 5h to obtain a carrier;
[0076] Step 2: Preparation of Ru-based catalyst
[0077] 4.4611 g of RuCl3·3H2O was dissolved in 65 mL of deionized water to obtain a Ru-based salt solution. The support was immersed in the Ru-based salt solution, dried at 120°C for 20 h, and then calcined at 500°C for 5 h to obtain the Ru-based catalyst, which was recorded as catalyst 7.
[0078] Catalytic performance verification
[0079] Catalysts 1-7 were used for the reaction of catalytic oxidation of HCl to prepare chlorine, and it was further clarified that the catalyst of the present invention had a catalytic effect significantly better than that of the comparative example through the synergistic effect of the modifier, the carrier, the co-catalyst and the active ingredient Ru group. The specific technical scheme is as follows:
[0080] Take 10 mL of catalysts 1-7 respectively and load them into the fixed bed reactor. Pass the mixed gas of HCl and O2 into the fixed bed reactor and set the gas space velocity to 5000 h -1 , wherein the molar ratio of HCl to O2 is 2:1, the reaction temperature is set to 300°C, the reaction is continued for 4 hours, the initial conversion rate of HCl is calculated, and then the reaction temperature is raised to 650°C for high-temperature catalytic deactivation of the catalyst. After deactivation for 10 hours, the temperature is lowered to 300°C again and the reaction is continued for 4 hours. The conversion rate and conversion rate retention rate of HCl after catalytic deactivation are obtained. The results are shown in Table 1.
[0081] Table 1. Initial conversion rate of HCl oxidation reaction catalyzed by catalysts 1-7, conversion rate of HCl after catalytic deactivation, and conversion rate retention rate.
[0082]
[0083] As can be seen from Table 1, the catalyst of the present invention has a significantly higher catalytic activity than the comparative example in the reaction of catalytic oxidation of HCl to prepare chlorine due to the synergistic effect of the Ru-based active center, the co-catalyst and the modified composite carrier, especially in comparative example 1, where the interaction between the modifier (Na2SO4 / Na3PO4) and the composite carrier (TiO2 / Al2O3) changes the surface acidity and alkalinity and electronic properties of the carrier, thereby optimizing the dispersion state of the active ingredients and the co-catalyst; in addition, the modified composite carrier not only provides dispersion and support for the active ingredients and the co-catalyst, but also participates in the catalytic reaction process, and the TiO 2 As the main carrier component, its rutile crystal form or the mixed crystal form of rutile and anatase has a specific crystal structure and surface properties, which is beneficial to the adsorption and desorption of reactants and products. At the same time, Al2O3 increases the thermal stability and mechanical strength of the carrier and adjusts the surface acidity of the carrier to make it more suitable for the adsorption and reaction of reactants, so that the stability of the catalyst in Example 1 is significantly higher than that of the comparative example. After high-temperature catalytic deactivation, the conversion rate retention rate is significantly higher than that of the comparative example, which proves that the catalyst of the present invention is significantly better than that of the comparative example in terms of catalytic activity, stability under high temperature conditions and life.
[0084] The catalysts prepared in Example 1 and Comparative Example 1 were applied to the catalytic oxidation of HCl to produce chlorine, keeping the gas component ventilation volume and reaction temperature unchanged. The two groups of reactions were sampled and tested every 4 hours, and the test results every 24 hours were averaged. After 1000 hours of continuous reaction, the stability of the catalyst was analyzed. The conversion rate trend chart is shown in FIG. Figure 1 , Figure 1 It shows that the invented catalyst has no obvious deactivation after 1000h of continuous reaction, indicating that the catalyst life of the present invention is significantly better than that of the comparative example, and is more suitable for long-term continuous operation in industrial production, avoiding the time and economic costs caused by frequent catalyst replacement.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A Ru-based catalyst, characterized in that The catalyst is composed of an active ingredient Ru, a promoter, and a modified composite carrier. In the catalyst, based on the total mass of the catalyst and calculated as a Ru element, the loading amount of Ru is 0.1-5wt%, based on the total mass of the catalyst and calculated as a metal element, the content of the promoter is 0-20wt%; the specific surface area of the catalyst is 50-300m 2 / g, when the catalyst catalyzes the oxidation of HCl to prepare chlorine, the initial conversion rate of HCl is ≤89.95%, the conversion rate of HCl after catalytic deactivation at 650°C is ≤86.24%, and the conversion retention rate is ≤95.88%.
2. A method for preparing the Ru-based catalyst according to claim 1, characterized in that: The method comprises the following steps: Step 1: Preparation of modified composite carrier The modifier is dissolved in deionized water to prepare a modifier solution; the carrier and the modifier solution are mixed, stirred evenly, kneaded, extruded, and then dried in an oven at 100-200° C. for 5-20 hours, and then calcined at 500-1000° C. for 2-10 hours to obtain the modified composite carrier; Step 2: Preparation of Ru-based catalyst The promoter is dissolved in deionized water, and a soluble salt of Ru is added to obtain a salt solution containing Ru groups. The modified composite carrier is immersed in the salt solution containing Ru groups, dried at 80-150° C. for 5-20 hours, and then calcined at 200-500° C. for 2-10 hours to obtain the Ru-based catalyst.
3. The method for preparing a Ru-based catalyst according to claim 2, characterized in that: In step 1, the modifier is a soluble sulfur-containing oxygen acid salt and / or a soluble phosphorus-containing oxygen acid salt, and the content of the modifier is 0-20wt% in terms of sulfur or phosphorus based on the mass of the catalyst; the carrier is a mixture of one or more of TiO2 and other metal oxides or non-metal oxides.
4. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In step 1, the soluble sulfur-containing oxygen-containing acid salt is selected from one or a mixture of more than one of sulfates, hydrogen sulfates, persulfates, pyrosulfates, sulfites, and thiosulfates of ammonium, lithium, sodium, potassium, cesium, magnesium, calcium, strontium, and barium; the soluble phosphorus-containing oxygen-containing acid salt is selected from one or a mixture of more than one of phosphates, hydrogen phosphates, dihydrogen phosphates, pyrophosphates, and acid pyrophosphates of ammonium, lithium, sodium, potassium, cesium, magnesium, calcium, strontium, and barium.
5. The method for preparing a Ru-based catalyst according to claim 3, characterized in that: In step 1, the non-metallic oxide is selected from any one of SiO2 and B2O3 or a mixture of two of them; the metal oxide is selected from any one of Al2O3, ZrO2, SnO2 or a mixture of two or more of them.
6. The method for preparing a Ru-based catalyst according to claim 2, characterized in that: In step 2, the promoter is selected from one or a mixture of two or more of soluble salts of alkali metals and / or chlorides, nitrates, acetates, formates, oxalates, sulfates, and phosphates of alkaline earth metals; the soluble salt of Ru is selected from one or a mixture of more than one of ruthenium chloride, ruthenium bromide, ruthenium iodide, ruthenium acetate, potassium chlororuthenate, and ammonium chlororuthenate.
7. The method for preparing a Ru-based catalyst according to claim 2, characterized in that: The molar ratio of the co-catalyst to Ru is (0.1-5):
1.
8. The method for preparing a Ru-based catalyst according to claim 2, characterized in that: The mass ratio of Ru and carrier is 1:(20-1000).
9. The method for preparing a Ru-based catalyst according to claim 2, characterized in that: In the XRD spectrum of the catalyst, characteristic diffraction peaks of rutile titanium dioxide (110), (004), (200), (105) and (211) appeared at 27.4°, 38.0°, 48.0°, 54.0° and 62.7°, proving that the TiO2 in the carrier is a rutile crystal form or a mixed crystal form of rutile and anatase. In the modified composite carrier, the TiO2 content is ≥40wt% based on the mass of the modified composite carrier.
10. A method for catalytic oxidation of HCl, characterized in that: The method uses the Ru-based catalyst described in claim 1, and the specific steps are as follows: The Ru-based catalyst is added to a fixed bed reactor, the reaction temperature is controlled at 300-400°C, and a mixed gas of HCl and O2 is introduced into the reactor at a gas space velocity of 5000-10000h -1 , wherein the molar ratio of HCl:O2 is (2-20):1, the reaction time is 4-30h at 300-400°C; then the reaction temperature is raised to 650-750°C for high temperature accelerated deactivation of the catalyst, and after deactivation for 10-20h, the temperature is lowered again to 300-400°C for continuous reaction for 4-30h; The initial conversion rate of HCl is ≤89.95%, the conversion rate of HCl after catalytic deactivation at 650°C is ≤86.24%, and the conversion retention rate is ≤95.88%.
Citation Information
Patent Citations
Ruthenium catalysts for the catalytic gas-phase oxidation of hydrogen chloride with oxygen (deacon method)
CN101663092A
Ruthenium dioxide catalyst for producing chlorine by oxidizing hydrogen chloride and preparation method thereof
CN109453764A